The Harkness Method in Teaching English Reading Skills - Moralishvili, Sophio; Chkhobadze, Isolda (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The presented article explores the innovative Harkness Method as a dynamic approach to teaching English reading skills. Originating from the progressive educational philosophy of Exeter Academy, the Harkness Method involves student-centered teaching through round-table discussions, creating an environment where students are actively engaged in text analysis and discussion. The Harkness Method was initially developed at Phillips Exeter Academy in the 1930s. It represents a student-centered approach to the learning process, focusing on collaborative, discussion-based teaching. The method was authored by Edward Harkness, a supporter of democratic teaching. Unlike traditional teaching approaches, which are teacher-led, the Harkness Method promotes critical thinking, collaborative analysis, and deep understanding, placing students in the roles of discussion leaders and participants. This study examines the effectiveness of the Harkness Method in improving English reading skills, asserting its productivity in developing students' interpretation, critique, and literature analysis abilities. Through qualitative data analysis, the article demonstrates how this pedagogical strategy enhances not only reading but also communication and analytical skills. The conclusion of the article notes that the Harkness Method offers a promising alternative to traditional reading instruction, making it a valuable tool for teachers whose primary goal is to create interactive teaching and reflective classroom experiences.